2015
DOI: 10.1590/s1677-5538.ibju.2014.0273
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pseudoexfoliation syndrome and erectile dysfunction: a possible cause of endothelial dysfunction for development of erectile dysfunction

Abstract: Objectives:Pseudoexfoliation syndrome (PES) is a common age-related fibrillopathy related to accumulation of pseudoexfoliation material (PEM) in certain places in the body, especially blood vessels. Erectile dysfunction (ED) is another condition related to vascular pathology and in this study it is aimed to identify the relationship between ED and PES.Materials and Methods:Data of 92 patients were investigated. There were 34 patients in the PES group and 58 patients in the control group. Presence of diabetes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…[7172] PEX is considered a systemic microfibrillinopathy closely linked to mutations in the lysyl oxidase-like 1 (LOXL1) gene,[51] with pseudoexfoliative material being found throughout visceral organs in affected individuals. [737475] Conjunctival biopsies of patients with unilateral PEX demonstrated microscopic disease in the unaffected fellow eye. [6] Our review of the literature has shown that clinically unaffected fellow eyes do not have significant differences in ECD compared to their paired eyes with PEX, with both showing similarly decreased ECD when compared to a group of age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…[7172] PEX is considered a systemic microfibrillinopathy closely linked to mutations in the lysyl oxidase-like 1 (LOXL1) gene,[51] with pseudoexfoliative material being found throughout visceral organs in affected individuals. [737475] Conjunctival biopsies of patients with unilateral PEX demonstrated microscopic disease in the unaffected fellow eye. [6] Our review of the literature has shown that clinically unaffected fellow eyes do not have significant differences in ECD compared to their paired eyes with PEX, with both showing similarly decreased ECD when compared to a group of age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review of positive risk factors for XFS in general [Tables 5 - 7 ][ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 ] and XFS in young subjects [ Table 8 ][ 82 83 84 85 86 87 88 89 90 91 …”
Section: Resultsmentioning
confidence: 99%
“…In the Lebanese cohort under investigation, XFS was associated with advanced age, glaucoma, habitual ocular rubbing, and longer time for cataract surgery. While advanced age [ Table 6 ],[ 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 ] glaucoma [ Table 5 ],[ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 ] and longer surgery duration[ 100 ] are well established risk factors for XFS [ Table 5 ],[ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 <...>…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies concerning ED and the eye have reported interesting findings. An independent relationship has been observed between ED and pseudoexfoliation syndrome (PXS) characterised by accumulation of fibrillary material, generally in the anterior part of the eye (Gokce & Gokce, 2015). Those authors reported a higher presence of ED and higher severity in the PXS‐positive group compared with the control group.…”
Section: Discussionmentioning
confidence: 99%